2024
DOI: 10.1038/s41467-024-45043-2
|View full text |Cite
|
Sign up to set email alerts
|

Human coronavirus OC43-elicited CD4+ T cells protect against SARS-CoV-2 in HLA transgenic mice

Rúbens Prince dos Santos Alves,
Julia Timis,
Robyn Miller
et al.

Abstract: SARS-CoV-2-reactive T cells are detected in some healthy unexposed individuals. Human studies indicate these T cells could be elicited by the common cold coronavirus OC43. To directly test this assumption and define the role of OC43-elicited T cells that are cross-reactive with SARS-CoV-2, we develop a model of sequential infections with OC43 followed by SARS-CoV-2 in HLA-B*0702 and HLA-DRB1*0101 Ifnar1−/− transgenic mice. We find that OC43 infection can elicit polyfunctional CD8+ and CD4+ effector T cells tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 146 publications
0
4
0
Order By: Relevance
“…Prolonged infections of mouse models with SARS-CoV-2 for an extended period may also provide valuable insights into LC development. Just recently, Dos Santos Alves and colleagues showed that human coronavirus OC43-elicited CD4+ T cells are protective against SARS-CoV-2 in HLA transgenic mice [72]. This validates that SARS-CoV-2-reactive T cells are detected in some healthy, unexposed individuals, just as other human studies indicate these T cells could be elicited by the common cold coronavirus OC43.…”
Section: Mouse Modelsmentioning
confidence: 71%
“…Prolonged infections of mouse models with SARS-CoV-2 for an extended period may also provide valuable insights into LC development. Just recently, Dos Santos Alves and colleagues showed that human coronavirus OC43-elicited CD4+ T cells are protective against SARS-CoV-2 in HLA transgenic mice [72]. This validates that SARS-CoV-2-reactive T cells are detected in some healthy, unexposed individuals, just as other human studies indicate these T cells could be elicited by the common cold coronavirus OC43.…”
Section: Mouse Modelsmentioning
confidence: 71%
“…An early, and Th1-leaning CD4+ T cell response is deemed important for combatting SARS-CoV-2 ( 59 ). Additionally, a study has shown that pre-existing CD4+ T cells induced from previous infection provided protection against SARS-CoV-2 ( 60 ). Similarly, IFNγ has demonstrated driving vaccine-induced cellular immunity in K18-hACE2 transgenic B-cell deficient (μMT) mice ( 61 ) and recently confirmed to induce early control of SARS-CoV-2 infection when administered intranasally to wildtype C57BL/6 mice ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed that pre-existing CD4 + T-cells in humans respond to pandemic 2009 H1N1 peptides, correlating with reduced virus shedding and milder illness during IAV infection [10]. Additionally, research confirms the existence of protective cross-reactive T-cell responses among human coronaviruses [11][12][13], mirroring the diverse protective effects of cross-reactive T-cells against the influenza virus (IV) [14,15]. Notably, specific memory T-cell populations boast an extended lifespan, with highly conserved T-cell epitopes, rendering viruses more prone to evading humoral immunity over T-cell immunity [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 93%